Hyperglycemia-induced activation of the hexosamine biosynthetic pathway causes myocardial cell death - Rajamani, Uthra (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Physiological Sciences))--University of Stellenbosch, 2009.